(untitled) (Palíndromo, 2017)
This article aims to contribute to an understanding of drawing that encompasses idea, graphic and thing. Perspectivated by the interest in the artistic process and considering the ideas of continuum and potency, the reflection propose the notion of convulsion as the dynamics that occurs between these three states.